(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: The rise in the prevalence and significance of non-communicable diseases (NCDs) is the result of complex interaction between health, economic growth and development. Knowledge about NCDs and appropriate practices related to NCDs are keys to its proper management. Objectives: To determine the level of knowledge about NCDs among the selected urban school students. Materials and Methods: A cross-sectional study was conducted among the students of Adamjee Cantonment Public School & Shaheed Bir Bikram Ramiz Uddin Cantonment School of Dhaka Cantonment during 01 January 2017 to 31 December 2017. A total of 183 participants were selected by purposive sampling technique. Data were collected using a pretested interviewer administered semi-structure questionnaires and SPSS version 22 used for data analysis. Simple descriptive statistics were used to describe the study variables. Inferential statistics were include, chi-square test, to find out any significant relationship between two qualitative variables. Results: Participants (n = 183) included 129 (70.49%) were male and 54 (29.51%) were female, aged between 13–19 years. Among 183 respondents, 106(57.9%) participants have good knowledge, 76(41.5%) participants had average knowledge and 1(0.5%) participant had poor knowledge. Level of knowledge had significant association with gender, age, education, father’s & mother’s occupational status, family income, physical activity, smoking & habit of taking hard drink. Conclusion: The knowledge and practices related to NCDs among the participants were good in certain aspects but poor in others, suggesting the need for programs on NCDs awareness. Comprehensive community based health education program about NCDs is necessary to improve this situation. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 90-93